Building Brand Identity: Social Media Strategies of Sovereign Wealth Funds and Recommendations for SOFAZ - Adamo, Aisha; Csapaiova, Rita; Tarhini, Chaza (ADA University, 2025)
The State Oil Fund of Azerbaijan (SOFAZ), faces an obvious gap in communication with the public, indicated by a lack of public awareness of the Fund's role, strategic objectives, and influence on the national economy. This study highlights the engagement challenges that SOFAZ is dealing with in the modern social media-driven world, mainly its weak presence on digital platforms, the lack of an engaging brand identity, and the inefficient use of modern digital marketing tools. The research focuses on analyzing three main problems: insufficient public awareness of the fund, the absence of an effective communication strategy, and low engagement rates on social media, with the failure to reach the target groups. This study aims to provide strategic solutions based on theoretical and practical foundations to enhance SOFAZ's performance in the domain of corporate communication, by Redefining the vision and mission in a Simple and straightforward way, and designing a new visual identity that Boost public trust and reflects transparency and professionalism. It also recommends developing a digital marketing strategy based on data analysis, including the use of artificial intelligence tools to analyze audiences, the application of content testing techniques (A/B testing), and the promotion of interactive content through live sessions, success stories, and simplified visual content. Furthermore, the study highlights the need to conduct an analysis of the target audience, including youth, policymakers, and investors, to ensure that communication messages are transmitted successfully. Through this research, a comprehensive structure is proposed to improve SOFAZ's company brand identity and increase public engagement by social media, thus enhancing transparency, accountability, and public trust in one of the country's most important economic institutions. The results indicate that developing a comprehensive and dynamic digital corporate communications strategy is a necessary step to ensure the sustainability of the Fund's economic and social impact and activate its role as an institution serving the public interest through strategic management of national wealth.
Keywords: Corporate communication -- Strategy -- Azerbaijan; Digital marketing -- Strategy -- Azerbaijan; Public relations -- Social media; Brand identity -- Azerbaijan; Azerbaijan -- Economic policy; Public and International Affairs